2009
DOI: 10.1007/s10800-009-9838-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical characteristics of boron doped polycrystalline diamond electrode sintered by high pressure and high temperature

Abstract: The bulk B-doped polycrystalline diamond (PCD) electrode in this study was prepared by high-pressure, high-temperature (HPHT) technology. The PCD was sintered under HPHT conditions, using B-doped diamond powders and a metal catalyst as raw materials, then the metal solvent phase was dissolved by aqua regia. The morphology and composition of the PCD were investigated with a scanning electron microscope (SEM), X-ray diffraction (XRD), and energy dispersion spectrum (EDS). The results show that the sintered body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The C C is the capacitance at the interface electrolyte/electrode at high frequencies [74,75], while the capacitance of the capacitor element (C d ) in the equivalent circuit is associated to the capacitance developed inside the micropores of the carbon electrode [74,76]. According to Table 4, it can be observed that PAC/PTS has the highest values of C C and C d among the electrodes studied; which C d represents the main contribution to the total electrode capacitance.…”
Section: Electrochemical Characterizationsmentioning
confidence: 99%
“…The C C is the capacitance at the interface electrolyte/electrode at high frequencies [74,75], while the capacitance of the capacitor element (C d ) in the equivalent circuit is associated to the capacitance developed inside the micropores of the carbon electrode [74,76]. According to Table 4, it can be observed that PAC/PTS has the highest values of C C and C d among the electrodes studied; which C d represents the main contribution to the total electrode capacitance.…”
Section: Electrochemical Characterizationsmentioning
confidence: 99%
“…Powder metallurgy is a promising method of synthesizing copper and copper composites due to its good densification and ease of operation with cost effective [1,10]. Powder metallurgy techniques have been used to synthesize copper and copper composite powders as well as other composites for different electronics applications [19,20]. Besides, there is virtually no reported study on the combined effects of tantalum and ruthenium on the mechanical properties of submicron copper and copper composites for interconnect materials, studies on similar copper based composites synthesized by high pressure high temperature is also very limited.…”
Section: Introductionmentioning
confidence: 99%